Validation of a realistic simulation scenario for teaching diagnostic reasoning in nursing consultation to patients with pulmonary tuberculosis (Research, Society and Development, 2021)
Tuberculosis still persists as a public health problem in Brazil and requires a complex approach from the nurse for the proper management of this disease. In this sense, the teaching of diagnostic reasoning during the nursing consultation must be carried out through effective methodologies, among which the realistic simulation. Objective: validate a realistic simulation scenario for teaching diagnostic reasoning in nursing consultations to patients with pulmonary tuberculosis. Method: this was a methodological development study, carried out from January to July 2021. The scenario was designed taking into account the items: simulation design, determination of results and objectives, facilitation, briefing, debriefing and participant evaluation, simulation and simulation-based experience. The validation step took place through the application of the Content Validation Index (IVC). A significance level of 5% was adopted for the binomial test and 0.80 as an acceptable proportion of agreement index for validation. Results: according to the I-CVI and applied binomial test, it was observed that all items were approved, with a minimum value of 0.88 of agreement proportion among the judges and with an average of 97% of approval among the experts. Conclusion: The realistic simulation scenario designed and validated for teaching diagnostic reasoning in nursing consultations to patients with pulmonary tuberculosis is characterized as an important methodological teaching tool in the education of nursing students and training of nurses with regard to care for patients with tuberculosis.